PENGARUH PRESTASI KERJA DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI PADA BAGIAN RAWAT INAP RUMAH SAKIT DAERAH MANGUSADA KABUPATEN BADUNG - Ni Luh Ayu Sumaria Dewi; I Ketut Sutapa (Universitas Triatma Mulya, 2022)
The Mangusada Regional Hospital has a good vision and mission in its planning but in reality the vision and mission are still experiencing obstacles and several obstacles, especially in the management of human resources, especially in the inpatient department, so this has become a problem that has not been resolved until now. This study aims to determine and analyze the effect of work performance and organizational climate on employee job satisfaction in the inpatient department of the Mangusada Regional Hospital, Badung Regency. Based on the results of statistical testing it was found that both simultaneously and partially the variables of work performance and organizational climate had a positive effect on employee job satisfaction in the inpatient department of the Mangusada Regional Hospital, Badung Regency. For this reason, the Mangusada Regional Hospital, Badung Regency, is advised to pay more attention to work performance factors and organizational climate together because these two factors have a major role in increasing or decreasing employee job satisfaction.